2022
DOI: 10.4314/tjpr.v21i7.11
|View full text |Cite
|
Sign up to set email alerts
|

Chrysoeriol alleviated inflammation in infantile pneumonia by inhibiting PI3K/AKT/mTOR signaling pathway

Abstract: Purpose: To assess the therapeutic effects of chrysoeriol (CHE) on pediatric pneumonia and determine the mechanism of action. Methods: The role of chrysoeriol was investigated in a human lung fibroblasts (HFL1) cell model of pneumonia. The effects of lipopolysaccharide (LPS) and CHE on cell viability and apoptosis were determined by CCK-8 kit and flow cytometry, respectively, while oxidative stress was determined by evaluating the levels of superoxide dismutase (SOD), glutathione, r-glutamyl cysteine +gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 16 publications
1
0
0
Order By: Relevance
“…The increased binding affinity of Chrysoeriol against the target is in accordance with the study conducted by Wonlkularb et al [15], wherein chrysoeriol has been shown to promote apoptosis in rat C6 glioma cells via suppression of the PI3K/Akt/mTOR signaling pathway, thereby demonstrating the potential antineoplastic effects of chrysoeriol on glioma cells. In another study by Wang et al, Chrysoeriol has been found to inhibit the PI3k pathway in pneumonia cells [20]. The results of these studies concurs with the findings of our study that the chrysoeriol has good binding affinity with PI3k-Ras binding protein.…”
Section: Discussionsupporting
confidence: 92%
“…The increased binding affinity of Chrysoeriol against the target is in accordance with the study conducted by Wonlkularb et al [15], wherein chrysoeriol has been shown to promote apoptosis in rat C6 glioma cells via suppression of the PI3K/Akt/mTOR signaling pathway, thereby demonstrating the potential antineoplastic effects of chrysoeriol on glioma cells. In another study by Wang et al, Chrysoeriol has been found to inhibit the PI3k pathway in pneumonia cells [20]. The results of these studies concurs with the findings of our study that the chrysoeriol has good binding affinity with PI3k-Ras binding protein.…”
Section: Discussionsupporting
confidence: 92%